الجيش الفرنسي و مجازر 8ماي 1945 بين الروايات الفرنسية والدراسة التاريخية - واضح,مداني (University of Eloued جامعة الوادي, 2025)
يعالج الموضوع محل البحث مجازر الثامن ماي1945 في الجزائر ،من خلال نقد الروايات الفرنسية المتداولة حول ما حدث ،والوقوف عندها وتحديدا الرواية الرسمية للإدارة الفرنسية ، التي تتحدث عن تحركات مشبوهة لبعض زعماء الحركة الوطنية عشية انتهاء الحرب العالمية الثانية ، وكيف حاولت الإدارة الفرنسية استغلالها من أجل دفع الجيش الفرنسي والقوات الأمنية الأخرى إلى القتل المفرط و اللامسؤول، لمتظاهرين جزائريين سلميين حتى قبل بداية المظاهرات، واستمر ذلك حتى بعد توقفها، متهمة حزب الشعب الجزائري بضلوعه فيها، والاتجاه بها نحو المنحى التصعيدي، الذي أصبح يهدد الوجود الفرنسي في الجزائر ،فجاءت هذه الدراسة للكشف عن مدى قصور الإدارة الاستعمارية في معرفة حقيقة هذه المظاهرات ، ومعرفة الثغرات التي كانت موجودة في هرم القيادة السياسية والعسكرية الفرنسية في الجزائر، واستغلالها من طرف المستوطنين لتحقيق مزيدا من الاستعمار ، ولذاك قمنا بعرض الروايات الفرنسية الرسمية المتداولة قبيل نهاية الحرب العالمية الثانية، ثم تحليلها من خلال التحضير العسكري والأمني للمجازر، باتهام حزب الشعب الجزائري بالتمرد للتبرير والشرعنة لعمليات القمع والإبادة، فكانت النتيجة استفزاز للعناصر الوطنية الجزائرية التي أصبحت تدعوا للاقتصاص والانضواء تحت راية الجهاد من أجل تحرير البلاد.The topic under discussion deals with the massacres of May 8, 1945 in Algeria, in terms of criticizing the French narratives circulating about what happened, and examining them, specifically the official narrative of the French administration, which talks about the political movements of some leaders of the National Movement on the eve of the end of World War II, and how the French administration tried to exploit them in order to push The French army and other security forces led to the excessive and irresponsible killing of peaceful Algerian demonstrators even before the demonstrations began. This study came to reveal the extent of the colonial administration’s failure to know the truth about these demonstrations, And the extent to which this was exploited by the settlers to achieve further colonization. Therefore, we presented the official French narratives circulating before the end of World War II, Then how did the military and security prepare for the massacres, by accusing the Algerian People’s Party of justifying and legitimizing the operations of repression and extermination. The result was a provocation to the Algerian national elements who began calling for retaliation and joining under the banner of jihad in order to liberate the country.
Keywords: حزب الشعب الجزائريذ; المجازر; المظاهرات; عمليات القمع; الإبادة الجماعية; الاستراتيجية العسكرية; Strategy; demonstrations; massacres; military reports; repressions; Genocide